The Pit-Prop Syndicate - Crofts, Freeman Wills, 1879-1957 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Pit-Prop Syndicate" by Freeman Wills Crofts is a mystery novel likely written during the early 20th century. The story revolves around Seymour Merriman, a junior partner in a wine merchants' firm, who encounters an intriguing situation while on a business trip in France. The narrative begins with Merriman's journey to Bordeaux, where a peculiar incident concerning a motor lorry and its changing number plate sparks his curiosity, hinting at a deeper mystery related to the operations of a sawmill. At the start of the novel, Merriman, feeling weary and disillusioned after a long ride, encounters a girl named Madeleine Coburn in a remote part of the forest. She helps him with his motorcycle troubles and invites him to the mill, which her father manages. However, Merriman becomes intrigued by the lorry he had seen earlier, marked with different numbers at different times. As he contemplates the implications of this change and the mysterious aura surrounding the Coburns, he decides to investigate further. The opening chapters set the stage for a mix of mystery and adventure as Merriman and his friend, Hilliard, plan to uncover potential secrets behind the mill's operations and the enigmatic number plates, while also exploring their burgeoning interests in the Coburns. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Pit-Prop_Syndicate
Release date is 1999-12-01
An Anonymous Project Gutenberg Volunteer and David Widger
Keywords: Detective and mystery stories; Police -- England -- Fiction; Murder -- Investigation -- Fiction; British -- France -- Fiction; Organized crime -- England -- Fiction